Altered Microbiota, Impaired Quality of Life, Malabsorption, Infection, and Inflammation in CVID Patients With Diarrhoea - van Schewick, Cornelia M.; Nöltner, Christina; Abel, Svenja; Burns, Siobhan O.; Workman, Sarita; Symes, Andrew; Guzman, David; Proietti, Michele; Bulashevska, Alla; Moreira, Fernando; Soetedjo, Veronika; Lowe, David M.; et al. (Frontiers in Immunology, 2020)
BACKGROUND: Diarrhoea is the commonest gastrointestinal symptom in patients with common variable immunodeficiency (CVID). OBJECTIVE: The aim of this study was to describe the prevalence and clinical presentation of chronic and recurrent diarrhoea in the Royal-Free-Hospital (RFH) London CVID cohort, including symptoms, infections, level of inflammation, and microbial diversity. METHODS: A Cross-sectional study of adult CVID patients (139 out of 172 diagnosed CVID). Those with diarrhoea ≥ 6 days/month had stool and blood samples analysed and completed the short Inflammatory Bowel Disease Questionnaire (sIBDQ). BMI, spleen-size, lymphocytes and gut-microbial diversity were compared. RESULTS: 46/139 (33.1%) patients had current significant diarrhoea. In patients with past or present diarrhoea, BMI was lower (median 23.7 vs. 26, p=0.005), malabsorption more common (57.97% vs. 35.71%, p=0.011). CD4+ lymphocytes were higher in patients with diarrhoea (p=0.028; n=138), but CD4+ naïve lymphocytes were significantly higher in non-diarrhoea patients (p=0.009, N=28). Nine patients had confirmed or probable current gastrointestinal infections. Calprotectin was >60 µg/g in 13/29 with significant diarrhoea including 9 without infection. SIBDQ revealed a low median score of 4.74. Microbial alpha diversity was significantly lower in CVID patients compared to healthy household controls. CONCLUSION: Patients with CVID and significant diarrhoea had infections, raised calprotectin, malabsorption, a lower BMI, an impaired quality of life (comparable to active IBD), and they differed from non-diarrhoea patients in their lymphocyte phenotyping. Furthermore, microbial diversity was altered. These findings strongly imply that there may be an inflammatory nature and a systemic predisposition to diarrhoea in CVID, which necessitates further investigation.